An investigation of the use and mis-use of preposition by ESL university learners in their written assignment / Fazlinda Hamzah and Mohd Azlan Shah Sharifudin - Hamzah, Fazlinda; Sharifudin, Mohd Azlan Shah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2017)
Studies have shown that learning prepositions is among the hardest for second language learners and this is especially true for learners of English. This study sought to analyse the errors related to the target prepositions ‘in’, ‘on’ and ‘at’ in English essays written by first year Centre for Language (CFL) students of the International Islamic College (IIC), to identify the possible sources of preposition errors and to find out if native language interference is a source of error related to the target prepositions. Fifty essays written by first year Malay students of IIC were used in this study and the topics of the essays centred on common human concerns such as family, friendship and marriage. The errors related to the prepositions ‘in’, ‘on’ and ‘at’ were identified and explained. Next, the sources of errors were analysed and presumed explanations were given. The findings of the study show that the students’ problem was mostly with the preposition ‘in’, followed by ‘at’ and lastly ‘on’. It was also found that native language interference was a probable source of errors related to the use of prepositions ‘in’, ‘on’ and ‘at’. The results of the study were also expanded to pedagogical implications such the use of suitable teaching materials, using Contrastive Analysis, exposure to language, error correction and using technology in teaching prepositions.